2019
DOI: 10.1186/s12891-019-2591-3
|View full text |Cite
|
Sign up to set email alerts
|

Footwear fit in schoolchildren of southern Spain: a population study

Abstract: Background Recent studies support the theory that ill-fitting shoes are an important source of pain and may lead to foot malformations in the medium term. Taking as reference the ideal allowance considered in the literature, the purpose of this study was to verify the outdoor footwear fit in a population of schoolchildren of southern Spain. Methods Five hundred and five children within the range of 3–12 years of age participated in this study. Using a measuring instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 18 publications
6
28
0
Order By: Relevance
“…Significant differences were found at 8 years of age, and from 10 to 12 years. Our results coincide with most observational studies that indicate that up to 8 years of age the foot grows predominantly in length, and after this age the width/length ratio in children is similar to that observed in adults [ 8 , 14 , 16 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Significant differences were found at 8 years of age, and from 10 to 12 years. Our results coincide with most observational studies that indicate that up to 8 years of age the foot grows predominantly in length, and after this age the width/length ratio in children is similar to that observed in adults [ 8 , 14 , 16 , 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…Most studies report that the growth rate of foot length decreased after 12–13 years in adolescent girls continued to increase up to the age of 15 years in adolescent boys. Feet of girls stop growing around 12–13 years of age, and in boys, around 13–15 years [ 4 , 5 , 6 , 7 , 8 , 14 , 15 ]. In studies with cohorts of Asiatic schoolchildren, this event seems to end somewhat later, lasting up to 15 years in girls, and up to 16 years in boys [ 18 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Zhang & Wang (2017) most children, especially in the early stages of ontogenesis, wear shoes that are too short. In our study, as many as 40% of girls and boys had shoes that were incorrectly fitted in length, which were often too short, while shoes that were incorrectly fitted in width were worn by as many as 74% of girls and 66% of boys (most of them used shoes that were too short), and the gender influence the obtained results González Elena & Córdoba-Fernández (2019) based on a study from southern Spain, found that 72% of the surveyed children aged 3-12 years old, regardless of gender, wore shoes that were too short, and 67% wore shoes that were too narrow. Yurt, Sener &Yakut (2014) andDelgado-Abellán et al (2014) analyzed the issues of footwear fit in terms of width.…”
Section: Discussionmentioning
confidence: 56%
“…The authors indicated that most footwear designs do not take into account the need to choose different widths for one length size. González Elena & Córdoba-Fernández (2019) concluded that when designing ergonomic footwear for schoolchildren, not only the different digital formulae must be taken into account, but also the position and orientation of the forefoot inside the shoe and its interaction with the shoe tip.…”
Section: Discussionmentioning
confidence: 99%